Pengaruh Budaya Organisasi, Lingkungan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Toyota Motor Manufacturing Indonesia (TMMIN) - Alifah Mutiara Safitri; Hendy Tannady (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to describe the influence of organizational culture, work environment and work discipline on employee at PT Toyota Motor Manufacturing Indonesia (TMMIN). This study uses quantitative methods by conducting a survey to 125 respondents. The sampling method is purposive sampling and uses the SPSS 20.0 data processing assistance program. This study has a very influential variable, namely organizational culture with a. regression coefficient of 0.249. from the result of this study it can be concluded that there is a partial and simultaneous influence oof the organizational culture variable, work environment and work discpline on employee performance at PT Toyota Motor Manufacturing Indonesia (TMMIN) and also held socialization about The Toyota Way to improve good insight, evaluate employees, as well as conduct mentoring, culture learning in career development to support good performance optimal.